2022
DOI: 10.1051/0004-6361/202141585
|View full text |Cite
|
Sign up to set email alerts
|

J1832.4-1627, the first eclipsing stream-fed intermediate polar

Abstract: We present a photometric study of the newly discovered eclipsing intermediate polar J183221.56-162724.25 (in short J1832) with an orbital period of 8.87 h. The system features a box-like deep eclipse with a full width at 50% depth of 1970 ± 2 s and a large-amplitude coherent pulsation with Pobs = 65.18 min, which represents either the synodic (beat) period or the spin period of the white dwarf (WD). The period ratio is either Pspin/Porb  =  0.1091 or 0.1225, respectively. The eclipsed light originates almost e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…More recently, low-accretion states have been detected in several confirmed or suspected IPs, including V1323 Her (Andronov et al 2014), FO Aqr (Littlefield et al 2016;Kennedy et al 2017), DW Cnc (Segura Montero et al 2020), Swift J0746.3-1608(Bernardini et al 2019Beuermann et al 2022), and YY Dra itself (Breus et al 2017), though as we noted in Section 3.3, the previously observed YY Dra low states do not show evidence of a cessation of accretion. Additionally, Covington et al (2022) have identified low states in V1223 Sgr, V1025 Cen, V515 And, and RX J2133.7 + 5107, and they conclude that low states in IPs are more common than previously realized.…”
Section: Comparison To Low States In Other Ipsmentioning
confidence: 62%
See 2 more Smart Citations
“…More recently, low-accretion states have been detected in several confirmed or suspected IPs, including V1323 Her (Andronov et al 2014), FO Aqr (Littlefield et al 2016;Kennedy et al 2017), DW Cnc (Segura Montero et al 2020), Swift J0746.3-1608(Bernardini et al 2019Beuermann et al 2022), and YY Dra itself (Breus et al 2017), though as we noted in Section 3.3, the previously observed YY Dra low states do not show evidence of a cessation of accretion. Additionally, Covington et al (2022) have identified low states in V1223 Sgr, V1025 Cen, V515 And, and RX J2133.7 + 5107, and they conclude that low states in IPs are more common than previously realized.…”
Section: Comparison To Low States In Other Ipsmentioning
confidence: 62%
“…Of the other IPs that have been observed in low states, only in J1832 has the accretion rate been observed to decline to negligible levels. Similar to YY Dra, J1832 shows no variability related to the WD's rotation during its deep low states (Beuermann et al 2022), but J1832 has the added advantage of being a deeply eclipsing system. Beuermann et al (2022) showed that when J1832 enters a deep low state, its optical eclipse depth becomes imperceptibly shallow, suggesting that there is no remaining accretion luminosity and hence no accretion.…”
Section: Comparison To Low States In Other Ipsmentioning
confidence: 97%
See 1 more Smart Citation
“…More recently, low-accretion states have been detected in several confirmed or suspected IPs, including V1323 Her (Andronov et al 2014), FO Aqr (Littlefield et al 2016;Kennedy et al 2017), DW Cnc (Segura Montero et al 2020), Swift J0746.3-1608(Bernardini et al 2019Beuermann et al 2022), and YY Dra itself (Breus et al 2017), though as we noted in Sec. 3.3, the previously observed YY Dra low states do not show evidence of a cessation of accretion.…”
Section: Updated Orbital Periodmentioning
confidence: 67%
“…Similar to YY Dra, J1832 shows no variability related to the WD's rotation during its deep low states (Beuermann et al 2022), but J1832 has the added advantage of being a deeply eclipsing system. Beuermann et al (2022) showed that when J1832 enters a deep low state, its optical eclipse depth becomes imperceptibly shallow, suggesting that there is no remaining accretion luminosity and hence no accretion. Due to gaps in ground-based observational coverage of J1832, it is unclear how long J1832's deep low states last or how long it takes for the system to fall into one.…”
Section: Updated Orbital Periodmentioning
confidence: 97%